Sex related disparities after complex percutaneous coronary interventions - Alperi, Alberto; Almendárez, Marcel; Pascual, Isaac; Alvarez, Rut; Betanzos, Jose Luis; Hernández-Vaquero, Daniel; Ptaszynski, Raul; Ortiz, Juan Francisco; Moris, Cesar; Avanzas, Pablo (Frontiers in Cardiovascular Medicine, 2024)
IntroductionComplex Percutaneous coronary intervention (PCI) for the treatment of ischemic heart disease has increased significantly. We aimed to evaluate sex-related differences in patients undergoing complex PCI.Methodssingle-center prospective observational study including patients undergoing complex PCI between 2017 and 2023. Baseline and procedural features, and mid-term outcomes were compared according to the gender distribution. The combined primary endpoint included stroke, myocardial infarction, need for a new coronary revascularization, and all-cause mortality. Propensity score (PS) matching with an inverse probability of treatment weight (IPW) approach was used to adjust for differences in baseline characteristics.Results1,283 patients were included, 983 (76.6%) male and 300 (23.4%) female. Median follow-up was 2.4 (IQR: 1–3.8) years. There was a higher rate of no-reflow phenomenon (4% vs. 1.8%, p = 0.03) among female patients. In the overall cohort, female patients had a greater risk for the combined primary endpoint (HR 1.28, 95% CI: 1.02–1.59). In the matched cohort, female patients exhibited a higher risk for the combined primary endpoint (HR 1.23, 95% CI: 1.06–1.42), as well as for myocardial infarction (HR 1.34, 95% CI 1.03–1.75), and all-cause mortality (HR 1.21, 95% CI 1.02–1.45), and a trend towards a higher risk for the need of a new coronary revascularization (HR 1.22, 95% CI 0.92–1.61).Conclusionsin a contemporary cohort of patients undergoing complex PCI procedures, female patients are associated with a higher risk of early complications.